171k views
1 vote
Select all of the expressions that are equivalent to: 21-i

Select all of the expressions that are equivalent to: 21-i-example-1

1 Answer

6 votes

Answer:

(3 - 2i)(5 + 3i)

Explanation:

if we multiply both parenthesis we can see that 21 - i = (3 - 2i)(5 + 3i)

First multiply 3 with (5 - 3i)

3 × (5 5 3i) = 15 + 9i

then we multiply -2i with (5 - 3i)

-2i × (5 + 3i) = -10i - 6i^2 since -i^2 is equal to -1 we can write the expression like this -10i + 6

now we find the sum of expressions

15 + 9i - 10i + 6 = 21 - i

User Brary
by
5.7k points